2006
DOI: 10.1212/01.wnl.0000194225.78917.de
|View full text |Cite
|
Sign up to set email alerts
|

Substrate reduction therapy in the infantile form of Tay-Sachs disease

Abstract: Substrate reduction therapy (SRT) with miglustat has been proposed for treatment of some lysosomal storage disorders. Based on the positive experience in Gaucher disease and experimental data in Tay-Sachs (TSD) and Sandhoff animal models, the authors investigated the clinical efficacy of SRT in two patients with infantile TSD. SRT could not arrest the patients' neurologic deterioration. However, a significant drug concentration in CSF as well as macrocephaly prevention were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 8 publications
2
50
0
3
Order By: Relevance
“…Glucosyl ceramide synthase inhibitors have already been approved for treatment of type I Gaucher disease and used in trials for Fabry disease, the GM2 gangliosidoses and Niemann-Pick disease (Patterson et al 2007). They have been proven in principle in TaySachs and SandhoV mice models (Jeyakumar et al 2002) and investigated in a clinical setting recently (Bembi et al 2006). These clinical as well as the in vitro data might also propose a possible application of these drugs in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Glucosyl ceramide synthase inhibitors have already been approved for treatment of type I Gaucher disease and used in trials for Fabry disease, the GM2 gangliosidoses and Niemann-Pick disease (Patterson et al 2007). They have been proven in principle in TaySachs and SandhoV mice models (Jeyakumar et al 2002) and investigated in a clinical setting recently (Bembi et al 2006). These clinical as well as the in vitro data might also propose a possible application of these drugs in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 In vivo studies have demonstrated the ability of miglustat to prevent storage of G M2 ganglioside in the peripheral tissues and central nervous system of mouse models of TSD and Sandhoff disease. 19,20 Case studies of miglustat in patients with infantile and subacute TSD have not detected slowing of neurological deterioration, 15,21 but in patients with the infantile form, a high concentration of miglustat is achieved in the patient's cerebrospinal fluid, associated with prevention of macrocephaly. 21 To date, no studies of other therapies for G M2 gangliosidosis have been reported.…”
mentioning
confidence: 99%
“…Mice treated with this drug showed delayed symptom onset, reduced storage in peripheral tissues and in the brain, and increased life expectancy. Based on these positive experimental data, Bembi et al (2006) investigated the clinical efficacy of N-butyldeoxynojirimycin in two patients with infantile Tay-Sachs disease (B variant of GM2-gangliosidosis). However, the enzyme inhibitor could not slow down the progressive clinical deterioration.…”
Section: Substrate Reduction Therapymentioning
confidence: 99%